POLITENESS STRATEGIS AND FACE THREATENING ACTS: THEIR ROLE IN SHAPING POSITIVE SOCIAL RELATIONSHIPS IN THE SERIES ‘BRIDGERTON’ - Shazkia Ananda Putri; Andi Anto Patak; Fatimah Hidayahni Amin (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2026)
The Bridgerton series, which has been airing on the Netflix platform since 2020, has attracted a lot of attention from viewers. The characters in the Bridgerton series not only use politeness strategies to interact but also to maintain good relationships as well as to maintain power in the social class differences that exist in the Bridgerton series. Therefore, this study aims to find the types of politeness strategies used by the Bridgerton series characters to avoid FTA and also to find out how the application of politeness can show the social status and social relationships of the characters. The research results were obtained using a descriptive qualitative method with conversation analysis approach. The use of Brown and Levinson's four politeness strategies in the Bridgerton series was found. The bald on-record, positive politeness, negative politeness, and off-record strategies are used by the characters to avoid facial threats. Positive politeness shows the use to avoid actions that can threaten a positive face and negative politeness shows the use to avoid actions that can threaten a negative face. While the bald on-record and off-record strategies show the use to avoid positive and negative face-threatening actions. The four strategies are also used by the characters in interactions with other characters who have social status and formal relationships and non-formal relationships. Positive politeness, and negative politeness strategies are used by the main characters when interacting with someone who has a higher social status and is in a formal social relationship. The bald on-record strategy is used by the characters when interacting with someone who has a lower social status and is in an informal social relationship. Meanwhile, the off-record strategy shows more flexible usage.